Relationship of Nurse Characteristics and Fulfillment of Client Service Rights in Installations - Ifon Driposwana Putra; Suharizal Suharizal; Emil Huriani (LPPM STIKES KENDAL, 2020)
Nursing practice requires nurses to be vigilant, aware and responsible for every action taken, be able to defend their actions and be willing to accept the consequences of those actions. One of the obligations of nursing practice is to fulfill the rights of client service. Various cases were exposed after the client or family complained about the services provided, but it is believed that the incidence is not small like the iceberg phenomenon, namely the visible problem is only a small part of a bigger problem. This study is to determine the relationship between nurses and the fulfillment of client service rights in inpatient installations. This type of research is quantitative with a correlational descriptive design, the study population was 122 people with a sample of 93 nurses with startified simple random sampling. Data were collected using a questionnaire to explore the characteristics of nurses and fulfillment of client service rights. The data were then analyzed by univariate and bivariate. The results showed 91.4% of young adult nurses, 72% of female sex, 71% of vocational education, 66.7% of juniors and 55.9% of clients did not fulfill client service rights. There is no relationship between age, sex and length of service of nurses with fulfillment of client service rights, and there is a relationship between nurse education level and fulfillment of client service rights.